Analisis Penggunaan Media YouTube dan Instagram pada Anggota Kelompok Suporter Sriwijaya FC dalam Mengonsumsi Informasi - Muhammad Fajar Wiko; Bayu Hardiono; Zakaria Wahab (JEMBATAN, 2020)
The study, entitled Analysis of the Use of YouTube and Instagram Media on Members of the Sriwijaya FC Supporter Group in Consuming Information, aims to determine the relationship between the profile and behavior of members of the Sriwijaya FC supporter group in using YouTube and Instagram as social media to consume information about their team. The method used in this research is descriptive-quantitative with crosstab analysis and chi-square test on SPSS software. The data in this study were collected through a questionnaire (google form) to 100 representatives from three members of the Sriwijaya FC supporter group, namely Singa Mania, Sriwijaya Mania, and Ultras Palembang. The results of this study indicate that duration on YouTube and audience involvement on Instagram are related to the efforts of members of the supporter's group to consume information about Sriwijaya FC.